Maximizing Indonesian Students’ Readability by Using English Textbooks - John Pahamzah; Syafrizal Syafrizal; Nurhaedah Gailea; Zakaria Zakaria (JETL (Journal of Education, Teaching and Learning), 2020)
The objective of the research was to find out whether the textbook provided by teachers had fulfilled the criteria of having a good book. The researcher used qualitative research, particularly content analysis research design. To answer the research questions, the researcher analyzed the contents of textbooks, evaluated by using a checklist adapted from the Cunningsworth checklist and writing a report. The researcher interpreted data to determine whether the textbook met the criteria for a good textbook. The results of the analysis showed that there were no textbooks that met the criteria for good books. The first result showed that the Think Global Act Locally met the criteria with a percentage of 51.92%, the coverage was 66.67% for aims and approaches, 33.33% for design, 40% for language content, 55.56% for skills, 66.67% for topics, 80% for methodology, 0% for teacher's book and 75% for practical considerations. The second was "English on Sky 3" met the percentage of 59.62%, the coverage was 66.67% for aims and approaches, 50% for design, 60% for language content, 72.22% for skills, 66.67% for the topic, 80% for methodology, 0% for Teacher's book and 50% for practical considerations. Meanwhile, Practices Your English Competence 3 met the percentage of 42.31%, the coverage was 33.33% for aims and approaches, 50% for design, 60% for language content, 33.33% for skills, 66.67% for topics, 60% for methodology, 0% for teacher's book and 50% for practical. In conclusion, there were no criteria that achieved good criteria and three out of eight criteria were considered fair.